Analisis struktur dan strategi pengembangan potensi ekonomi di kota samarinda - Aries, Rudi; Juihardi, Juihardi; Gani, Irwan (INOVASI, 2016)
The aim of this research was to analyses the economic structure and determined development strategy depend PDRB growth and labour absorption of Samarinda City compared with PDRB and Labour absorption in East Kalimantan Province. The analysis method in this research was the analysis of Shift Share that aimed at knowing the economy structure and how achievement productivity economy with compared with province economy. The economy structure of Samarinda City based development growth strategy with in growth or IMG and competivness effect or RSG analysis showed that trade, hotel and restaurant sector is the main economy sector could gave highest for PDRB and transportation and communication sectors is the best categories contribution at labour absorption.Keyword: Economy structure, economy potency, competitive, development strategy PDRB Growth and labour absorption at Samarinda City